Delivering Biophilic Urbanism: Tools and Strategies for Implementation - Cabanek, Agata (Curtin University, 2021)
Global interest in biophilic urbanism and design is growing and a number of cities around the world are working towards becoming more biophilic. This thesis is designed to support that process through the evaluation of potential strategies and tools for the efficient and financially-viable delivery of biophilic urbanism. A multiple-case study research approach was used to answer the research questions. The results provide urban planners and stakeholders with a basis for enabling and stimulating wider uptake.